The radio channel in the vehicular identification - Meneses, Ricardo; Linares, Roberto; Montes, Laura (Kathmandu University Journal of Science Engineering and Technology, 2010)
The Radio Frequency Identification System, a wireless communication system, recently it is being applied to vehicular identification, the radio electric and geometry environment characteristics influence the Radio Channel, which one, have been analyzed extensively in different papers, but no one of them has analyzed the RFID technology applied to vehicular technology. The radio channel model is necessary for the effective design of transmitters and receivers, and to determining the positions of the tag and the reader. This motivates the analysis of the propagation environment for outdoor RFID systems. In order to know a feasible RFID application to the vehicular identification, a set of tests were implemented in laboratory and in the field, in order to obtain a channel model that predicts the average power level, a semi-stochastic model, where the average power level is given by the distance raised to some power that depends on the environment, and the field strength in an area around a transmitter, and take into account the structure and materials used at every location in the area. As a result from these tests, the RFID signal and the RFID channel behavior are the focus and discussion of this article.